The use of biological disease-modifying antirheumatic drugs and Janus kinase inhibitors in rheumatoid arthritis during the COVID-19 coronavirus disease pandemic: data from a telephone survey of 254 patients - A. E. Karateev; E. Yu. Polishchuk; A. S. Potapova; E. V. Matyanova; A. S. Semashko; А. O. Bobkova; E. S. Filatova; V. N. Amirjanova; S. I. Glukhova; E. G. Zotkin; A. M. Lila (Научно-практическая ревматология, 2022)
The prescribing of biological disease-modifying antirheumatic drugs (bDMARDs) and Janus kinase inhibitors (iJAK) during the COVID-19 pandemic requires a balanced approach and tight monitoring of the patients.The aim of the study was to study the effect of bDMARDs and iJAK inhibitors on the condition of patients with rheumatoid arthritis (RA), taking the patients reported outcomes, as well as the incidence of COVID-19 in these patients.Materials and methods. A telephone survey was conducted of 254 patients with RA (average age – 49.8±13.7 years; 64.4% of patients are positive for rheumatoid factor; women – 83.5%; DAS28 score – 5.4±1.6 points), who in the period from January 2020 to June 2021 were prescribed bDMARDs or iJAK for the first time: 148 (58.3%) – rituximab; 57 (22.4%) – tumor necrosis factor α inhibitors; 20 (7.9%) – iJAK; 17 (6.7%) – interleukin 6 inhibitors; 12 (4.7%) – abatacept.Results. At the time of the survey, 204 (80.3%) patients continued taking prescribed medications. The main reason for the interruption of treatment was administrative problems. Synthetic DMARDs (mainly methotrexate and leflunomide) were received by 68.0%, glucocorticoids – 45.3%, nonsteroidal anti-inflammatory drugs – 44.5% of respondents. Among patients treated with bDMARDs or iJAK, 68.1% noted «the state of symptoms acceptable to the patient», the absence of frequent joint pain – 65.3%, the absence of increased fatigue – 14.3%. The incidence of COVID-19 and hospitalization associated with this disease did not differ in individuals who continued and stopped using bDMARDs or iJAK: 41.2% and 44.6%, 13.7% and 14.0%, respectively (p=0.80884). There were no statistically significant differences in the incidence of COVID-19 and hospitalization associated with this disease in patients taking various bDMARDs or iJAK.Conclusion. Despite the COVID-19 pandemic, rituximab remains one of the most popular bDMARDs. About a third of patients receiving bDMARDs or iJAK are not satisfied with their condition. More than 40% of patients who received these drugs suffered COVID-19; 14.0% required hospitalization.